A novel heating strategy and its optimization of a solar heating system for a commercial building in term of economy. (15th April 2021) - Qiu, Guodong; Yu, Shipeng; Cai, Weihua
Abstract: The existing solar heating system has high cost and a poor economy and is difficult to popularize because it needs a large area of solar collector and a volume of storage tank. Although many researchers attempted to optimize the system, it still could not reduce the initial cost significantly. To solve this problem, this paper presented a novel heating strategy for a specific commercial building and optimized it in term of economy. The novel strategy adopts a time-share heating method to reduce the initial cost and operating cost according to the heating requirement of the specific commercial building. In this study, a general model of a solar heating system based on TRNSYS was established. The combined effect of collector area, storage tank volume and electricity price on the economy was analyzed. The optimal matching ratio between storage tank volume and the collector area was obtained, and the heating performance in optimal matching was evaluated. The results showed that when the electricity price is $ 0.12, Vt /Ac  = 0.05 has the maximum net present value (NPV), which has good economy with 6 years of payback period. This study presented an effective approach to solve the economic problem of solar heating.